Influence of a paint coating on the corrosion of hull plates made of mild steel in natural seawater - Karunaivel Kavipriya; Nilavan Anitha; Veerapandian Velkannan; Susai Rajendran; Caslav Lacnjevac (Zaštita Materijala)
The corrosion resistance of mild steel (used to make hull plates in ship technology) in seawater before paint coating (Nippon paint, weatherbond advance) and after paint coating has been measured by electrochemical studies such as Polarisation study and AC impedance spectra. It is observed that after paint coating, the corrosion resistance of mild steel hull plates increases. Polarization study reveals that after paint coating, the linear polarization resistance increases and corrosion current decreases. AC impedance spectra reveal that in the presence of paint coating charge transfer resistance value increases, impedance value increases, phase angle increases and double layer capacitance value decreases.